Brill's Companion to Ancient Geography - Bianchetti, Serena. (Brill's Companions to Classical Studies., 2015)
Brill's Companion to Ancient Geography edited by S. Bianchetti, M. R. Cataudella, H. J. Gehrke is the first collection of studies on historical geography of the ancient world that focuses on a selection of topics considered crucial for understanding the development of geographical thought. In this work, scholars, all of whom are specialists in a variety of fields, examine the interaction of humans with their environment and try to reconstruct the representations of the inhabited world in the works of ancient historians, scientists, and cartographers. Topics include: Eudoxus, Dicaearchus, Eratosthenes, Hipparchus, Agatharchides, Agrippa, Strabo, Pliny and Solinus, Ptolemy, and the Peutinger Map. Other issues are also discussed such as onomastics, the boundaries of states, Pythagorism, sacred itineraries, measurement systems, and the Holy Land.